Kontribusi Intrapersonal Skills dan Interpersonal Skills Terhadap Kesiapan Kerja Pada Mahasiswa Perguruan Tinggi “X” - entot suhartono; zaky machmuddah (Sains Manajemen: Jurnal Manajemen Unsera, 2020)
The low quality of human resources in Indonesia is evidenced by the high level of unemployment in Indonesia. Data from the Central Statistics Agency show that open unemployment in Indonesia at the last high school level was 1.93 million, at the vocational level at 1.73 million, at the Diploma level at 220,932 and at the Bachelor level at 729,601 (BPS, 2018) . This phenomenon illustrates that labor readiness is still low in Indonesia. Higher education plays an important role to improve this. Producing graduates who are superior, skilled and have full competence in themselves is the main goal of every college. Empirically proving the relationship between intrapersonal skills and interpersonal skills to work readiness in "X" college students is the aim of this study. The method used in this research is survey. The population in this study were all "X" college students. The sample used in this study was "X" college final semester students. Purposive sampling with accidental sampling is a sampling technique used in this study. Multiple linear regression in the SPSS program is used as a data processing tool. Obtained 185 respondents in this research. Simultaneous test results show that intrapersonal skills and interpersonal skills affect work readiness for "X" college students. Partially intrapersonal skills and interpersonal skills, both of them affect the work readiness of "X" college students. The implication of this research is the importance of education related to soft skills because this greatly contributes to students preparing themselves when joining the workforce.Keywords: intrapersonal skills, interpersonal skills, work readiness.